Konsep Etos Global Hans Küng dan Relevansinya terhadap Upaya Dialog Antaragama di Indonesia - Georg Ludwig Kirchberger (Institut Filsafat dan Teknologi Kreatif Ledalero, 2022)
In the first place this article describes the background for the global ethos declared by the parliament of world religions in Chicago in 1993. That background is the parliament of religions itself and Hans Küng, the originator of the global ethos project, who with his team at Tübingen wrote the draft for the declaration. After that, the contents of the declaration on global ethos are discussed according to the two principles and five values put forward. In the second part, reflections are made on the relevance of this declaration on global ethos for interreligious dialogue in Indonesia. This ethos can only be implemented in a long process in which each religion explores its respective tradition to find the motivation for implementing that ethos. The results of this research and deepening need to be shared between religions in dialogue, which helps them to complement and support each other. Finally, it is emphasized that the Indonesian Philosophy and Theology Association should participate in intellectual research on the values of global ethos from a Christian perspective and should form networks with research institutes and universities from other religions to further promote understanding and working together between different religions in Indonesia and Asia. Keywords: Parliament of world religions, global ethos, Hans Küng, AFTI, interreligious dialogue